À propos de l’entretien mené avec Richard Long en septembre 2014 - Hoël Gaboriau (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This text is a commentary inspired by an interview with Richard Long by conservation-restoration students from l’École supérieure des beaux-arts de Tours and Fine Art students from l’université de Bordeaux. The interview was held in English on the 19th September 2014 at the CAPC in Bordeaux an is published in French translation here. This took place after the remake de White Rock Line made in 2014 after a restoration study took place in the École supérieure des beaux-arts de Tours.